Monitoring Monitoring Dual Koneksi VPN Memanfaatkan Netwatch Mikrotik Dan Notifikasi Bot Telegram Pada PT. Star Cosmos: Monitoring Dual Koneksi VPN Memanfaatkan Netwatch Mikrotik Dan Notifikasi Bot Telegram - dwi iswanto; Irwan Agus Sobari (OKTAL : Jurnal Ilmu Komputer dan Sains, 2022)
A network administrator at PT. Star Cosmos is not always in the monitoring room to monitor the current state of the network. In the event of a disturbance, the user informs via telephone or chat with the network administrator. This results in the handling of disturbances being longer, with the implementation of monitoring dual VPN connections using the Mikrotik Netwatch and Telegram bot notifications at PT. Star Cosmos is expected to be able to provide information to network administrators regarding network disturbances in real-time, especially in the head office network and branch offices that apply dual VPN technology. The method is to utilize the Mikrotik Netwatch facility and telegram bot notifications to inform network conditions to the network administrator's cellphone. As a result, a network administrator can find network conditions in real-time from Telegram notifications sent by Mikrotik even though they are not in the monitoring room. If there is a network disruption, the network administrator can immediately make repairs so that the handling process is faster because they always get notifications on their Telegram.